Good times, bad times: A closer look at the relationship between savoring and self-compassion. (November 2022) - Schellenberg, Benjamin J.I.; Semenchuk, Brittany; Bailis, Daniel S.; Strachan, Shaelyn; Quach, Allen
Abstract: Self-compassion is associated with many positive outcomes and is generally viewed as an adaptive way of responding during difficult times. But self-compassion has also been positively associated with savoring, a way of responding to positive experiences that involves attempting to sustain or intensify positive emotions, and little is known about the direction of this relationship or whether it generalizes to responses immediately after a positive event. We conducted two studies to learn more about the directionality (Study 1) and generalizability (Study 2) of this relationship. In Study 1, athletes ( N  = 298) completed assessments of self-compassion and savoring capacity at two time-points throughout a season. We tested a cross-lagged panel model and found that self-compassion predicted increases in savoring, but savoring did not predict change in self-compassion. In Study 2, sports fans ( N  = 244) reported the extent to which they engaged in savoring immediately after their favorite team had won a championship game. The results showed that self-compassion was positively associated with savoring following the game. Overall, this research reveals more about the directionality and generalizability of the relationship between self-compassion and savoring, and shows that the effects of self-compassion extend to the positive side of the human experience. Highlights: Self-compassion predicted increases in savoring over 2 months (Study 1). Savoring did not predict change in self-compassion over 2 months (Study 1). Self-compassion predicted greater savoring after a positive event (Study 2).